Efficacy of Garlic Extract (Allium sativum L.) as a Therapeutic Modality of Condyloma Acuminata: A Meta-Analysis - Lestari, Andriani Fuji; Satya Wydya Yenny (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Condyloma acuminata (CA) is a sexually transmitted infection caused by human papillomavirus (HPV). Current standard treatment has limitations, so effective and safe alternative therapies are needed. Garlic (Allium sativum L.) has long been used in traditional medicine and has potential as an antiviral and antitumor agent. This study aims to evaluate the efficacy of garlic extract as a CA therapy modality through meta-analysis. Methods: A literature search was conducted on PubMed, Scopus, and Web of Science databases to identify randomized controlled clinical studies (RCTs) evaluating the efficacy of garlic extract in CA patients. Extracted data included study characteristics, interventions, sample size, clinical outcomes, and side effects. Statistical analysis was performed using Review Manager 5.4 software. Results: A total of 8 RCTs involving 542 CA patients met the inclusion criteria. Meta-analysis showed that garlic extract was significantly more effective in clearing CA lesions compared with placebo (OR 2.87; 95% CI 1.95-4.23; p < 0.00001). Garlic extract also demonstrated comparable effectiveness to standard therapies such as podophyllin and imiquimod. There was no significant difference in the incidence of side effects between the garlic extract group and the control group. Conclusion: Garlic extract is an effective and safe therapeutic modality for CA. Further studies with more robust designs are needed to confirm these findings and explore the mechanism of action of garlic extract on CA.